Ethanolic Extract of Averrhoa carambola Leaf Has an Anticancer Activity on Triple-Negative Breast Cancer Cells: An In Vitro Study - Oscar F. Beas-Guzmán; Ariana Cabrera-Licona; Gustavo A. Hernández-Fuentes; Silvia G. Ceballos-Magaña; José Guzmán-Esquivel; Luis De-León-Zaragoza; Mario Ramírez-Flores; Janet Diaz-Martinez; Idalia Garza-Veloz; Margarita L. Martínez-Fierro; Iram P. Rodríguez-Sanchez; Gabriel Ceja-Espíritu; et al. (Pharmaceutics)
Background/Objectives: Averrhoa carambola, or star fruit, is a shrub known for its medicinal properties, especially due to bioactive metabolites identified in its roots and fruit with anti-cancer activity. However, the biological effects of its leaves remain unexplored. This study aimed to assess the effects of ethanolic extract from A. carambola leaves on triple-negative breast cancer (TNBC), an aggressive subtype lacking specific therapy. Methods: Phytochemical analysis and HPLC profile and additional cell line evaluation employing MDA-MB-231 were carried out. Results: Phytochemical screening revealed that the ethanolic extract was rich in flavonoids, saponins, and steroids, demonstrating an antioxidant capacity of 45%. 1H NMR analysis indicated the presence of flavonoids, terpenes, and glycoside-like compounds. Cell viability assays showed a concentration-dependent decrease in viability, with an IC50 value of 20.89 μg/mL at 48 h. Clonogenic assays indicated significant inhibition of replicative immortality, with only 2.63% survival at 15 μg/mL. Migration, assessed through a wound healing assay, was reduced to 3.06% at 100 μg/mL, with only 16.23% of cells remaining attached. An additive effect was observed when combining lower concentrations of the extract with doxorubicin, indicating potential synergy. Conclusions: These results suggest that the ethanolic extract of A. carambola leaves contains metabolites with anti-cancer activity against TNBC cells, supporting further research into their bioactive compounds and therapeutic potential.